2020
DOI: 10.3390/rs13010039
|View full text |Cite
|
Sign up to set email alerts
|

Instance Segmentation for Large, Multi-Channel Remote Sensing Imagery Using Mask-RCNN and a Mosaicking Approach

Abstract: Instance segmentation is the state-of-the-art in object detection, and there are numerous applications in remote sensing data where these algorithms can produce significant results. Nevertheless, one of the main problems is that most algorithms use Red, Green, and Blue (RGB) images, whereas Satellite images often present more channels that can be crucial to improve performance. Therefore, the present work brings three contributions: (a) conversion system from ground truth polygon data into the Creating Common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 121 publications
1
25
0
4
Order By: Relevance
“…1: Representation of the seasonal variations among center pivots in a Sentinel-2 image using the Red, Green, and Blue spectral bands. approaches: (a) detection of the core point of the center pivot [47]; (b) object detection with the establishment of bounding boxes around CPIS [20], [57]; (c) semantic segmentation that performs a pixel-wise classification where all CPIS pixels receive a label [18], [58], [59]; and (d) instance segmentation that produces bounding boxes and pixel-wise segmentation masks on CPIS [17].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…1: Representation of the seasonal variations among center pivots in a Sentinel-2 image using the Red, Green, and Blue spectral bands. approaches: (a) detection of the core point of the center pivot [47]; (b) object detection with the establishment of bounding boxes around CPIS [20], [57]; (c) semantic segmentation that performs a pixel-wise classification where all CPIS pixels receive a label [18], [58], [59]; and (d) instance segmentation that produces bounding boxes and pixel-wise segmentation masks on CPIS [17].…”
Section: Related Workmentioning
confidence: 99%
“…However, Detectron2's Mask-RCNN algorithm requires labels in the COCO annotation format [67], in which each image tile needs a JSON file with the corresponding annotations. Thus, we applied the method used by de Carvalho et al [17] to convert polygonal GIS data into the instance segmentation annotation format. Each object acquired a unique value from 1 to N, with N being the total number of CPIS.…”
Section: Annotations and Splitmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach is an effective alternative to construction inspection, requiring periodic data and free satellite imagery. Previous studies on PV panel detection have not yet shown reasonable solutions for classifying large regions, and the use of mosaicking with sliding windows is a promising solution [85][86][87].…”
Section: Introductionmentioning
confidence: 99%